Marijuana and madness - Castle, David J.; Murray, Robin, MD, M Phil, MRCP, MRC Psych; D'Souza, Deepak Cyril (Cambridge ; New York : Cambridge University Press, 2012)
'The second edition of this critically acclaimed and award-winning text provides a comprehensive overview of the psychiatry and neuroscience of Cannabis sativa (marijuana). It outlines the very latest developments in our understanding of the human cannabinoid system, and links this knowledge to clinical and epidemiological facts about the impact of cannabis on mental health. Clinically focused chapters review not only the direct psychomimetic properties of cannabis, but also the impact consumption has on the courses of evolving or established mental illnesses such as schizophrenia. Effects of cannabis on mood are reviewed, as are its effects on cognition. This new edition has been extensively updated and expanded with 10 new chapters to incorporate major new research findings. This book will be of interest to all members of the mental health team, as well as to neuroscientists, epidemiologists, public health specialists and those involved in drug and alcohol research'--
Machine generated contents note: Foreword; Preface; Part I. Pharmacology of Cannabis and the Endocannabinoid System: 1. The cannabinoid system from the point of view of a chemist Raphael Mechoulam and Lumir Hanus; 2. The function of the endocannabinoid system Roger Pertwee; 3. How cannabis works in the brain Leslie Iversen; Part II. The Changing Face of Cannabis: 4. The epidemiology of cannabis use: an international perspective Sandeep Chawla; 5. Is cannabis becoming more potent? Mahmoud ElSohly and David Potter; 6. Health policy and cannabis Wayne Hall and Louisa Degenhardt; Part III. Cannabis and the Brain: 7. Cannabis, endocannabinoids and neurodevelopment Ismael Galve-Roperh; 8. The impact of pubertal exposure to cannabis on the brain: a focus on animal studies Miriam Schneider; 9. Cannabis and cognition: short and long-term effects Nadia Solowij; 10. Does cannabis cause lasting brain damage? Nadia Solowij, Murat Yucel, Valentina Lorenzetti and Dan Lubman; Part IV. Cannabis, Anxiety and Mood: 11. Acute and subacute psychiatric effects of cannabis David Castle and Nadia Solowij; 12. The association between cannabis use and depression Louisa Degenhardt, Wayne Hall, Michael Lynskey, Carolyn Coffey and George Patton; 13. Cannabis and bipolar disorder Carol Silberberg and David Castle; Part V. Cannabis and Psychosis: 14. Cannabis and psychosis proneness Jim van Os, Helene Verdoux and David Castle; 15. Genetic factors that moderate the psychomimetic effects of cannabis Marta Di Forti, Robin M. Murray and Cecile Henquet; 16. Cannabis causes positive, negative, cognitive symptoms and produces impairments in electrophysiological indices of information processing Mohini Ranganathan, Andrew Sewell, Daniel Mathalon and D. Cyril D'Souza; 17. The neural basis for the acute effects of cannabis on learning and psychosis Sagnik Bhattacharrya and Phil McGuire; Part VI. Cannabinoids and Schizophrenia: Aetiopathology and Treatment Implications: 18. Does cannabis cause schizophrenia? Stan Zammit, Mary Cannon and Robin M. Murray; 19. Postmortem studies of the brain cannabinoid system in schizophrenia Suresh Sundram, Brian Dean and David Copolov; 20. The endogenous cannabinoid system in schizophrenia Paul Morrison; 21. The endocannabinoid system as a target for pharmacotherapy of schizophrenia Markus Leweke; Part VII. Cannabis and its Impact on Schizophrenia: 22. Acute effects of cannabis in established schizophrenia Cecile Henquet and D. Cyril D'Souza; 23. Cannabis and the long-term course of schizophrenia Don Liszen, Bart Peters and Lieuwe De Haan; 24. Motives that maintain cannabis use in schizophrenia Kim Meuser; 25. Treatment interventions for cannabis abuse in people with psychosis Wynne James and David Castle; Part VIII. Integration: 26. Cannabis and mental illness: an integration D. Cyril D'Souza, Robin M. Murray and David Castle; Index.
Includes bibliographical references and index.
Keywords: Marijuana -- Physiological effect; Marijuana -- Psychological aspects; Marijuana abuse -- Complications; Psychoses -- Etiology; Schizophrenia -- etiology; MEDICAL / Mental Health